Develovment Of Video Tutorials To Making Embroidery Terawang For Embroidery Courses - Yuliarma; Yeyen Julaini (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2021)
This research aims to develop a video tutorial for Embroidery Terawang, so that students are able to understand and carry out learning activities independently during activities from home. This type of research is research and development, while the research method used is the 4D development model which consists of define, design, development and disseminate, but in this research it only reaches the development stage. The data in this study are primary data obtained from a questionnaire on the validity and practicality of the product. The validity of the product was carried out by 2 media validators and 2 material validators. The subjects in this study were 1 lecturer for the embroidery course, 15 students for the small group trial and 50 students for the large group trial consisting of D-III and S1 students in the Department of Family Welfare Science in the year of entry. 2020. The product produced from this study is the Embroidery Terawang video tutorial in the Sulaman course with a validity test value obtained by a percentage of 84.13% with a very valid category. Meanwhile, the practicality test for the subject supervisory lecturers obtained a percentage of 91.6% with the very practical category, the small group practicality test was 87% with the very practical category and the large group practicality test obtained a percentage of 87.7% with the very practical category. Based on the research results, it can be concluded that the Embroidery Terawang video tutorial in the Embroidery course for fashion students of the FPP-UNP Family Welfare Science Department developed is very valid and very practical.